IMPLEMENTING GOOGLE CLASSROOM IN ENGLISH LEARNING AT STIT AL-ITTIHADIYAH LABUHANBATU UTARA - Gumarpi Rahis Pasaribu (Universitas Islam Lamongan, 2021)
The use of technology in the learning process is something that is always used. In the industrial era 4.0, the lecturer is required to have sufficient ability to keep up with technological developments. Learning that focuses on face-to-face processes must be integrated with blended learning. This condition makes Google as one of the largest web tools to introduce Google Classroom (GC) in 2014. The existence of GC is expected to be a solution to problems such as the lack of English lesson hours at the junior high school level. But unfortunately, there is still a lecturer who still does not know about the benefits of GC. So that through this service, it is hoped that it can provide a holistic picture related to the use of GC, especially in learning English. Further, this service is expected to improve student's English language skills which include listening, speaking, reading, and writing skills. The dedication method is carried out in four stages, namely: a) analysis stage, b) material preparation stage, c) implementation stage, and d) activity report preparation stage. The result of this service is that all participating lecturer is not familiar with GC, so the lecturer is very enthusiastic and interested in using GC. Lecturer knows the platforms that they can use in learning that is integrated with blended learning. The lecturer can more easily manage class assignments quickly and provide feedback to students effectively.